A test model of a power grid with battery energy storage and wide-area monitoring - Cai,L; Thornhill,NF; Kuenzel,S; Pal,B (IEEE Transactions on Power Systems, 2019)
This paper presents a test model for investigating how to coordinate a power grid and Energy Storage Systems (ESSs) by Wide-Area Monitoring (WAM). It consists of three parts: (1) a model of a power grid containing different types of generators, loads and transmission network; (2) a model of lithium-ion battery ESSs; (3) a model of multivariate statistical analysis based WAM built to capture the grid information for guiding the operation of ESSs. Simulation studies using a reduced equivalent model specifically built for a UK power grid enhanced with lithium-ion battery ESSs and WAM illustrate the way in which WAM can coordinate a power grid and ESSs, and also demonstrate the benefit of ESSs on a power grid.